Playtime rhymes: ladybird (Ladybird Books Ltd China, 1997)
"Playtime Rhymes" is a delightful children's book that features a collection of playful and engaging rhymes centered around various activities and games that children enjoy. Each rhyme captures the joy of play, encouraging movement, imagination, and interaction. The rhythmic and catchy verses are designed to be fun to read aloud, making it perfect for storytime or group activities. With colorful illustrations complementing the text, the book promotes language development and a love for reading while celebrating the energy and creativity of playtime.